Limbodessus moni sp. nov., a new high altitudinal diving beetle from the Grasberg in West Papua, Indonesia (Coleoptera: Dytiscidae, Bidessini) - Surbakti, Suriani; Balke, Michael; Hendrich, Lars (Zootaxa, 2023)
Limbodessus moni sp. nov. is described from Lake Anderson and from small, richly vegetated swampy areas around alpine lakes at 3,970 m a.s.l. near the Grasberg Mine (Carstensz Pyramid) in the Central Mountain Range of New Guinea. The record of the new species marks the altitudinal maximum of a diving beetle in New Guinea. The new species is morphologically similar to L. alexanderi Balke & Hendrich, 2015 in terms of body size and dark coloration; however, both species can be easily separated by the shape of the median lobe and the more moniliform female antennomeres, not forming a conspicuous club as in L. alexanderi. A modified key for all five Limbodessus species from New Guinea and adjacent islands is presented.